Foreign experience in using logistics, marketing management and the possibility of its adaptation in Ukraine (Economics and region, 2019)
The article is devoted to the study of foreign experience in the field of logistics and marketing management. The authors disclose the results of the analysis of the rating of countries by the LPI index, as well as identify the problems of Ukraine, which cause its low rating on this indicator. The article offers suggestions on the possibilities of implementing foreign experience in modern logistics management to improve the Ukrainian logistics system.
Keywords: logistics; logistics management; marketing management; logistics performance index (LPI); logistics market; logistics process management